Artemisinin-resistant K13 mutations rewire Plasmodium falciparum’s intra-erythrocytic metabolic program to enhance survival - Sachel Mok (Nature Portfolio, 2021)
The emergence and spread of artemisinin resistance has compromised antimalarial efficacy. Here, Mok et al. apply quantitative transcriptomics, proteomics, and metabolomics to provide evidence that K13 mutations alter multiple aspects of the parasite’s intra-erythrocytic development to enhance survival following artemisinin treatment.